The EU and crisis response - Mac Ginty, Roger; Pogodda, Sandra; Richmond, Oliver P. (Manchester University Press, 2021)
This is a start-of-the-art consideration of the European Union's crisis response mechanisms. It brings together scholars from a range of disciplinary backgrounds to examine how and why the EU responds to crises on its borders and further afield. The work is based on extensive fieldwork in among another places, Afghanistan, Libya, Mali and Iraq.The book considers the construction of crises and how some issues are deemed crises and others not. A major finding from this comparative study is that EU crisis response interventions have been placing increasing emphasis on security and stabilisation and less emphasis on human rights and democratisation. This changes - quite fundamentally - the EU's stance as an international actor and leads to questions about the nature of the EU and how it perceives itself and is perceived by others.The volume is able to bring together scholars from EU Studies and Peace and Conflict Studies. The result showcases concept and theory-building alongside case study research.